2015
DOI: 10.1186/s40942-015-0010-y
|View full text |Cite
|
Sign up to set email alerts
|

Endophthalmitis following intravitreal anti-vascular endothelial growth factor (VEGF) injection: a comprehensive review

Abstract: The purpose of this review is to report and summarize previously reported studies and assess many of the individual steps of the intravitreal injection procedure’s possible effect on the prevention of endophthalmitis. The pooled endophthalmitis rate from 20 large retrospective case series of anti-VEGF injections was 144/510,396 (0.028%; 1/3,544). Injections may be performed in an office-based location or in an operating room (OR) and low rates of endophthalmitis can be achieved in either location with careful … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 202 publications
2
59
0
7
Order By: Relevance
“…In a recent audit of Medicare 5% claims data, Hahn et al (2016) found an increased risk of endophthalmitis after cataract surgery in patients who were undergoing regular anti-VEGF injections. During the earlier part of the audit period, the ASRS PAT survey data suggest that pre-and/or postinjection antibiotic administration was common practice (Merani & Hunyor 2015). Due to limitations in the data set, it is not clear whether the cases of endophthalmitis in this study were related to vitreous loss during cataract surgery, or if they occurred after subsequent intravitreal injections.…”
Section: Antibiotic Resistancementioning
confidence: 85%
See 1 more Smart Citation
“…In a recent audit of Medicare 5% claims data, Hahn et al (2016) found an increased risk of endophthalmitis after cataract surgery in patients who were undergoing regular anti-VEGF injections. During the earlier part of the audit period, the ASRS PAT survey data suggest that pre-and/or postinjection antibiotic administration was common practice (Merani & Hunyor 2015). Due to limitations in the data set, it is not clear whether the cases of endophthalmitis in this study were related to vitreous loss during cataract surgery, or if they occurred after subsequent intravitreal injections.…”
Section: Antibiotic Resistancementioning
confidence: 85%
“…Since the introduction of intravitreal antivascular endothelial growth factor (VEGF) agents, the exponential increase in the number of intravitreal injections has seen a considerable body of evidence established with regard to postinjection endophthalmitis (Merani & Hunyor 2015). The extremely low incidence of this complication means that randomized controlled trials examining the effectiveness of individual measures to prevent endophthalmitis are not feasible.…”
Section: Introductionmentioning
confidence: 99%
“…Intravitreal injections are also being performed with greater frequency for the treatment of neovascular disorders and inflammation (Peyman et al, 2009). In the United States, the number of intravitreal injections has increased from 4,215 in 2001 to 2.5 million in 2011, with similar increases reported for Canada and the United Kingdom (Merani and Hunyor, 2015). The rate of injection-related complications has also increased, with endophthalmitis incidences after intravitreal injection reported to be 0.006-0.16% per injection and 0.7-1.3% per treatment period (Diago et al, 2009; Klein et al, 2009; Sampat and Garg 2010; VEGF Inhibition Study in Ocular Neovascularization (V.I.S.I.O.N.)…”
Section: Clinical Aspects Of Bacterial Endophthalmitismentioning
confidence: 71%
“…While studies regarding postinjection pain scores are few and far between, we have found two suggestions for minimizing postinjection pain. Merani & Hunyor (2015) suggest using lubricant preservative-free eyedrops one day before the injection to reduce pain levels. The use of 30-gauge needles has been reported to reduce pain scores in another study (G€ uler et al 2015).…”
Section: Outcomes Eyementioning
confidence: 99%